Analysis of the state of the system of physical training of future law enforcement officers and perspective directions of its improvement - Kompaniets Yu.A (Kharkov National Pedagogical University, 2012)
The analysis of maintenance and orientation of scientific researches is conducted, programmatic and normative providing in the field of the applied physical training of students of higher educational establishments of Ministry of internal affairs of Ukraine. In researches 58 sportsmen took part in age from 17 to 22. It is rotined that the amount of clock on the special physical training can not provide the decision of the tasks put before it. It is set that from a crisis situation there can an exit be the wide use of different types of athletic activity (educational, sporting, recreational, rehabilitation). For them priority of spirituality and integrity of internal psychical life of man is characteristic in the process of forming of his physical standards. It is well-proven that optimum terms for complex athletic work are created during a leadthrough with the students of the camp field collection. Offered change in the chart of organization of educational process.